Guessing game method in speaking instruction - Anggun Pertiwi (ELT in Focus, 2023)
The aim of this research was to investigate in depth the use of the guessing game method in speaking learning, as well as the advantages and disadvantages of the guessing game method in speaking learning and the result of the use of the guessing game method in the process of speaking learning of the students in Junior High School 1 Karawang Barat. The research method is a case study with a qualitative approach. From the overall students in Junior High School 1 Karawang Barat, the data were obtained from the sample that was selected based on specific criteria, which was 4 students and 1 teacher. In data collection techniques, observation, interview, and documentation were used as the instruments for eliciting the data. The data taken were analyzed through three stages: data reduction, data display, and drawing conclusions or verification. Finally, after analyzing the data in depth, the results show that the use of the guessing game method in speaking learning worked well and that students were active during class speaking learning. The guessing game method of speaking has its advantages and disadvantages. The implementation of the guessing game method in speaking and learning showed excellent results. The students had increased ability, knowledge, and skill in speaking English.